Pelatihan Bisnis Kreatif Pembuatan Kerajinan Tangan dari Anyaman Pandan untuk Peningkatan Kapasitas Masyarakat Desa Wonorejo - Asroriyah, Atik Muhimatun; Nurhadi, Akhmad; Mugiastuti, Eka; Rahmadani, Arnila Dinar; Khoerunnisa, Maulida Rahmah; Wijayanto, Rori; Putri, Rizqiana; Andriyani, Fitri; Kurniawan, Rizki; Sayitno, Sayitno; Awanda, Regani Rio (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
Creative business training based on handicrafts from woven pandanus is an effort to empower the Wonorejo Village community to improve economic capacity and skills. This article describes a training program that involves community needs observation and intensive training in pandan weaving. Through this training, participants are equipped with technical skills starting from the material preparation stage to making innovative products such as mats, bags and baskets. In addition, participants were also provided with knowledge on digital marketing strategies to expand market reach. The results of the training showed an increase in community skills, with 85% of participants able to master basic techniques in a short time. Some community groups have also started to form small pandanus-based businesses that have the potential to create new jobs. This program not only supports economic independence, but also strengthens awareness of sustainable local resource management. The implementation of this training is a sustainable local wisdom-based community empowerment model, providing significant social and economic impacts for the Wonorejo Village community